Demographics and Economic Burden of Nasopharyngeal Carcinoma Inpatients. (15th June 2022) - Yang, Dong; Bin, Nengfu; Zhou, Ziyan; Li, Zhiru; Shen, Mingjun; Yang, Chaolin; Qin, Yating; Wang, Rensheng; Lv, Wei; Wei, Bo; Zhou, Lifang; Kang, Min
Abstract : Objective . Nasopharyngeal carcinoma is particularly prevalent in Guangdong and Guangxi (southern China); the economic burden of nasopharyngeal cancer patients is heavy in China. This study is aimed at retrospectively analyzing the basic features and economic burden of newly diagnosed nasopharyngeal carcinoma patients admitted to the First Affiliated Hospital of Guangxi Medical University and at providing a scientific basis for nasopharyngeal carcinoma prevention and control strategies. Methods . The data of 3, 727 nasopharyngeal carcinoma inpatients diagnosed from January 2012 to December 2020 were extracted from the Guangxi Nasopharyngeal Carcinoma Healthcare Big Data Management Information Platform. Basic demographic characteristics, duration of hospital stay, and hospitalization cost of nasopharyngeal carcinoma patients were collected and analyzed statistically. Results . The incidence period of nasopharyngeal carcinoma was primarily from 30 to 69 years of age, with the 40–49-year age group comprising the largest proportion of nasopharyngeal carcinoma patients, accounting for 34.18% of the patients with newly diagnosed nasopharyngeal carcinoma in the hospital. The male-to-female ratio was 2.87 : 1. There were 2, 223 cases from rural areas, 2, 153 from the Han ethnic group, and 1, 460 from the Zhuang ethnic group, accounting for 59.65%, 55.77%, and 39.17% of the total number of cases, respectively. The average duration of hospitalization decreased whereas the average hospitalization cost increased annually. Multivariate analysis of hospitalization cost showed that the duration of hospital stay, rural/urban, and ethnicity was the main influencing factors: the longer the duration of hospital stay, the higher the hospitalization cost; patients from rural incurred lower costs than from urban; ethnic Zhuang patients incurred significantly lower costs than patients from other ethnicities. Conclusion . Early diagnosis and treatment should be actively carried out to reduce the incidence of nasopharyngeal carcinoma, especially for rural, ethnic Zhuang, and males in the 40–49-year age group patients. The future research on nasopharyngeal carcinoma will focus on exploring the pathogenesis of nasopharyngeal carcinoma, improving the screening system, and reducing the burden on patients, in order to further improve the survival rate and quality of life of patients with nasopharyngeal carcinoma.